Correlation between the Insertion Side of a Transcondylar Screw for the Surgical Management of Humeral Intracondylar Fissures in Dogs and the Incidence of Postoperative Surgical Site Infection - Potamopoulou, Maria; Brown, Gordon; Whitelock, Richard (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective An increased rate of surgical site infection (SSI) following treatment of canine humeral intracondylar fissure (HIF) with a lateromedially (LM) placed transcondylar screw (TCS) compared with a mediolateral (ML) TCS has been previously postulated. We hypothesized that the direction of insertion of the TCS would not affect the incidence of postoperative SSI.Study Design It was single-centre retrospective study. Dogs with HIF confirmed by computerized tomography, treated by TCS placement (between 2008 and 2019) and with a minimum follow-up of 12 weeks, were included. The following data were recorded: signalment, presenting clinical signs, direction of placement and size of the utilized TCS, surgical and anaesthetic times, concurrent surgical procedures, presence of concomitant elbow pathology, perioperative and postoperative antibiotic usage and postoperative complications. Recorded data were analysed with a multinomial logistic regression model with a p-value less than or equal to 0.05.Results Thirty-five dogs (46 elbows) met the inclusion criteria. Median clinical follow-up interval was 52 weeks. Seven of thirty-one elbows with a ML TCS, and 4/15 elbows with a LM TCS developed SSI. Four of nine dogs that underwent bilateral single-surgery TCS placement developed SSI unilaterally.Conclusion No significant difference was shown in short-term SSI occurrence between the ML and the LM direction of placement of the TCS.
Keywords: dog; humeral intracondylar fissure; transcondylar screw; transcondylar screw direction; surgical site infection